SUITABILITY OF VARIOUS BUFFERS FOR GENOMIC DNA EXTRACTION OF PINEAPPLE (Ananas comosus) VAR. MD2 - Fifi Hafizzah, Pendi; Hasnain, Hussain (Penerbit UMT, 2020)
Methods for DNA extraction are of paramount importance to obtain high yield and high purity nucleic acids for molecular characterisation downstream. However, there is no specific extraction protocol developed for Ananas comosus var. MD2. Here, we compare the efficiency of five selected DNA extraction buffers which are extensively used for plant deoxyribonucleic acid (DNA) extraction with absence usage of phenol. The suitability of the extraction buffers was assessed based on both DNA yield and its quality. In this study, DNA extracts were quantified using ultraviolet (UV) spectrophotometry, spectrophotometric profiles and gel electrophoresis. Since interfering background substances are not visible in gel electrophoresis, examining PCR products of the crude DNA is recommended. To summarise, all the buffers yielded sufficient DNA of an approximate 50-200 μg from 1 g leaf tissue for downstream applications with different quality level. Out of five extraction methods, two give high yield and high-quality genomic DNA using Dellaporta-based method (213.5 μg/g) and Doyle & Doyle-based method (172.5 μg/g). Among these extraction methods, the exclusion of detergents in extraction buffer served as the best extraction buffer for MD2 genomic DNA extraction. Also, from an economic point of view, the extraction buffer is cheaper compared to commercial DNA extraction kits.